A contribution of fishermen's wives in increasing income: contribution of fishermen's wives in increasing income - Anita Indrianingsih; Heminuddin; Purnamasari, Elly (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
ABSTRAK Anita Indrianingsih, 2023.Fisherman's Wife's Contribution In Increasing Family Income In Kolo Village, Asakota District Bima City west Nusa Tenggara. (Supervised by Helminuddin and Elly) Purnamasari